IL‐9 inhibits HTB‐72 melanoma cell growth through upregulation of p21 and TRAIL. Issue 8 (18th May 2015) - Fang, Yujiang; Chen, Xuhui; Bai, Qian; Qin, Chenglu; Mohamud, Abdimalik O.; Zhu, Ziwen; Ball, Tyler W.; Ruth, Caleb M.; Newcomer, Dylan R.; Herrick, Elizabeth J.; Nicholl, Michael B.
<x xml:space="preserve">Abstract</x> Background IL‐9 is a pleiotropic cytokine produced mainly by Th9 cells. IL‐9 may have an anti‐proliferative role in murine melanoma, however, its effect on human melanoma is unknown. Methods We examined the effects of IL‐9 on proliferation and apoptosis in four human melanoma cell lines, HTB‐65, HTB‐72, CRL‐11147, and SK‐Mel‐5. Clonogenic assay, PCNA staining, Quick Cell Proliferation assay, TUNEL staining and caspase‐3 activity assay were used to assess proliferation and apoptosis, as appropriate. Results We found that IL‐9 decreased the percentage of colonies of HTB‐72 and SK‐Mel‐5 cells but not that of HTB‐65 or CRL‐11147 cells. PCNA mRNA, PCNA+ cells, PCNA staining intensity, and the OD value of HTB‐72 melanoma cells were consistently decreased in the present of IL‐9. IL‐9 also increased TUNEL+ cells and the relative caspase‐3 activity in HTB‐72 melanoma cells. We further investigated the possible molecular mechanisms using RT‐PCR and immunohistochemical staining. The anti‐proliferative effect of IL‐9 on HTB‐72 cells correlated with higher expression of anti‐proliferative molecule p21. Its pro‐apoptotic effect on HTB‐72 cells correlated with higher expression of the pro‐apoptotic molecule TRAIL. Conclusions IL‐9 inhibits melanoma HTB‐72 cell growth by upregulation of p21 and TRAIL. Understanding the interactions between IL‐9 and melanoma may help direct strategies for cytokine‐based immunotherapy development. J. Surg. Oncol. 2015 111:969–974. © 2015 Wiley Periodicals, Inc.